A global-scale framework for hydropower development incorporating strict environmental constraints - Xu, Rongrong; Zeng, Zhenzhong; Pan, Ming; Ziegler, Alan D.; Holden, Joseph; Spracklen, Dominick V.; Brown, Lee E.; He, Xinyue; Chen, Deliang; Ye, Bin; Xu, Haiwei; Jerez, Sonia; et al. (Nature Water, 2023)
The benefits of developing the world’s hydropower potential are intensely debated when considering the need to avoid or minimize environmental impacts. However, estimates of global unused profitable hydropower potential with strict environmental constraints have rarely been reported. In this study we performed a global assessment of the unused profitable hydropower potential by developing a unified framework that identifies a subset of hydropower station locations with reduced environmental impacts on the network of 2.89 million rivers worldwide. We found that the global unused profitable hydropower potential is 5.27 PWh yr−1, two-thirds of which is distributed across the Himalayas. Africa’s unused profitable hydropower is 0.60 PWh yr−1, four times larger than its developed hydropower. By contrast, Europe’s hydropower potential is extremely exploited. The estimates, derived from a consistent and transparent framework, are useful for formulating national hydropower development strategies.